SPE Annual Technical Conference and Exhibition 2019
DOI: 10.2118/196126-ms
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Ultrasonic Borehole Imaging Enhances Reservoir Evaluation in Oil-Based Muds

Abstract: Obtaining high-resolution borehole images in oil-based mud (OBM) from logging-while-drilling (LWD) tools has been made possible through the recent development of ultrasonic imaging technologies. High-resolution acoustic impedance images enable reservoir evaluation through the identification of faults and fractures, bedding and laminations, and assessment of rock fabric. This paper presents examples of high-resolution images from a 4¾-in. ultrasonic imaging tool in OBM applications and discusses their value in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…To improve the operation efficiency and reduce the extraction time, Equation ( 2) can be rewritten into Equation (6). In this way,…”
Section: Real-time Head-wave Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the operation efficiency and reduce the extraction time, Equation ( 2) can be rewritten into Equation (6). In this way,…”
Section: Real-time Head-wave Extractionmentioning
confidence: 99%
“…To improve the operation efficiency and reduce the extraction time, Equation ( 2) can be rewritten into Equation (6). In this way,N 2 L /N 2 S can be set as a constant, which is then directly stored into the register, and x(i) 2 and x(i − 1)•x(i + 1) can also be calculated in parallel.…”
Section: Real-time Head-wave Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonic LWD tools are routinely employed for obtaining high resolution images of the borehole wall with one of the important objectives directed at detecting the presence of fissures on the surface of the borehole wall. The imaging resolution of such fissures however is typically very low even for high-resolution LWD tools (Li et al, 2019), partly because of the hardware limitations in incorporating such tools with the BHA. These ultrasonic LWD tools typically map the amplitude and travel time of the echo from the borehole wall for imaging.…”
Section: Fissure Geometry Estimationmentioning
confidence: 99%
“…A high SNR of about 30 dB can be observed between the region with influx (the orifice) and the regions away from the influx. Conventional backwall-amplitude images as used in LWD tools (Li et al, 2019) were also generated from the same orifice plates as shown in Figs. 16(b) and 16(d).…”
Section: Fissure Geometry Estimationmentioning
confidence: 99%